Discovering The Effect of Work From Home and Work Life Balance on Employees’ Work Motivation - Deliza Rahmadona Andera; Odang Kusmayadi (Peneliti.net, 2023)
This research was conducted with descriptive, verification and quantitative approaches. The population in this study was 202 of the total employees who worked on a Work From Home basis and the sample used was 134 people, so the sampling technique used was non-probability sampling saturated sampling type. Data analysis will use the help of statistical software, SPSS version 26. The results of the descriptive analysis show that all the variables which are Work From Home, Work Life Balance, and Work Motivation are included in the